Grado de adherencia al tratamiento antidepresivo en pacientes ambulatorios de salud mental del Hospital Nacional Edgardo Rebagliati Martins, setiembre-diciembre, 2016 - Castillo Rodríguez, Evelyn Karito (2018)
The objective of this study was to determine the degree of adherence to the antidepressant treatment of mental health outpatients at the Edgardo Rebagliati Martins National Hospital, September-December, 2016. The sample consisted of 50 patients, older than 18 years old, with major antidepressant treatment. or equal to 1 month that she attended the outpatient clinic for depression control or any consultation associated with her, the data of interest was collected through the Morisky-Green-Levine test. The processing and analysis of data was done through the program using Microsoft Excel software. Fifty valid surveys were obtained, of these 34 patients presented low adherence representing 68%, 10 patients presented average adherence giving 20% and 6 patients presented high adherence representing 12% of the total sample. It is concluded that the degree of adherence to antidepressant treatment is low in outpatients of the mental health service of the Edgardo Rebagliati Martins National Hospital